The Homotopy Type of the Space of Degree 0 — Immersed Plane Curves - Kodama, Hiroki; Michor, Peter W. (Revista Matemática Complutense, 2006)
The space Bi = Imm0 (S 1 , R2 )/ Diff (S 1 ) of all immersions of rotation degree 0 0 0 in the plane modulo reparameterizations has homotopy groups 1 (Bi ) = Z, 0 0 2 (Bi ) = Z, and k (Bi ) = 0 for k 3.
Keywords: homotopy groups; immersed plane curves 2000 Mathematics Sub ject Classification; Primary 58D10; 58D29; 55Q52